3D printing of concentrated alginate/gelatin scaffolds with homogeneous nano apatite coating for bone tissue engineering. (15th May 2018) - Luo, Yongxiang; Li, Yuxiao; Qin, Xialing; Wa, Qingde
Abstract: Biomimetic nano apatite/polymer composite scaffolds with good mechanical properties and desirable bioactivity are promising for bone tissue engineering. Here, concentrated alginate/gelatin scaffolds with homogeneous nano apatite coating were developed utilizing 3D printing and in situ mineralization. The thickness of nano apatite coating was controlled by adjusting the amount of phosphate ions in the printing inks. The alginate/gelatin scaffolds with uniform nano apatite coating had 2-fold higher Young's modulus compared with the scaffolds without apatite coating. In addition, nano apatite coating significantly stimulated the proliferation and osteogenic differentiation of rat bone marrow stem cells. Furthermore, nano apatite coating increased the protein adsorption on the surface of scaffolds. The fabricated biomimetic nano apatite/hydrogel composite scaffolds would be potential candidates for bone tissue engineering. Graphical abstract: Unlabelled Image Highlights: Concentrated alginate/gelatin scaffolds with nano apatite coating were created via 3D printing and in situ mineralization. 3D printing controlled the morphology, and in situ mineralization was efficient to produce nano apatite on the surface. The nano apatite coated alginate/gelatin scaffolds exhibited enhanced Young's modulus and protein adsorption. The nano apatite stimulated the proliferation and osteogenic differentiation of rat bone marrow stem cells on the scaffolds.